Programmable photonics for optical communications: Looking at silicon photonics from a different perspective. Issue 4 (1st September 2022) - Gonzalez, Ana; Theodoras, Jim
Abstract: As the bandwidth requirements in communication networks continue to increase unabated, wafer level photonic integration is becoming key to miniaturizing components and increasing the number of functionalities, thereby replacing bulky systems. However, a variety of challenges such as long development times and high costs of fabrication are impeding the widescale adoption of this technology in the optical communication field.